Reassessment on Germination Requirements of Pinus kesiya Royle ex Gord. Seeds under Controlled Laboratory Conditions - L. KHARLUKHI; R.C. LALOO; A.L.S. RAJEE (Seed Research, 2026)
Seeds of Pinus kesiya Royle collected in February, 1998, were incubated at 20, 25 and 30° C temperatures on different substrata, namely, sand, top-of-paper and between rolled towel paper. For sand and top-of-paper, complete dark and alternate (16 hrs dark and 8 hrs light) treatment were given; seeds in between rolled towel paper experienced only dark treatment. For seeds on sand and top-of-paper observations were recorded on every alternate day for radicle and needle-shoot emergence, whereas for those in between rolled towel paper daily observations were recorded. From the data collected value of different indices, namely, Maguire Germination Rate Index (GRI), Peak Value and Czabator Germination Value (GV) were calculated separately for radicle and needle-shoot emergence. It was observed that of all combinations of temperature and dark/dark-light treatment, the most favourable combination for radicle emergence was that of 25°C on sand with dark-light treatment, which showed the highest GRI, Peak Value and GV, being 23.20, 17.33 and 72.01, respectively. For needle-shoot emergence, the same combination of treatment as for radicle emergence, showed the highest GRI and GV, being 6.27 and 9.33, respectively; the Peak Value failed to differentiate the most favourable environment from less favourable ones. From the final radicle emergence, it was evident that all the temperatures were favourable for sand substratum with dark-light combination, whereas the final needle-shoot emergence was most favoured by sand substratum with dark-light combination at 25°C; as a compromise 25°C incubation temperature, sand with dark-light combination may be recommended for germination test under laboratory conditions for seeds of Pinus kesiya should evaluation be done on the 21 day of incubation.